2016
DOI: 10.4236/aces.2016.63024
|View full text |Cite
|
Sign up to set email alerts
|

An Accurate and Computationally Efficient Explicit Friction Factor Model

Abstract: The implicit Colebrook equation has been the standard for estimating pipe friction factor in a fully developed turbulent regime. Several alternative explicit models to the Colebrook equation have been proposed. To date, most of the accurate explicit models have been those with three logarithmic functions, but they require more computational time than the Colebrook equation. In this study, a new explicit non-linear regression model which has only two logarithmic functions is developed. The new model, when compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 22 publications
3
43
0
2
Order By: Relevance
“…Brkić (2011a), Winning & Coole (2013) and Offor & Alabi (2016) analyzing explicit equations of the f, found that the RE values of Rao & Kumar's (2007) equation were the highest in relation to all the explicit equations analyzed in their research, being consistent with what was obtained in this study.…”
Section: Methodssupporting
confidence: 86%
See 3 more Smart Citations
“…Brkić (2011a), Winning & Coole (2013) and Offor & Alabi (2016) analyzing explicit equations of the f, found that the RE values of Rao & Kumar's (2007) equation were the highest in relation to all the explicit equations analyzed in their research, being consistent with what was obtained in this study.…”
Section: Methodssupporting
confidence: 86%
“…Models 2,3,5,9,14,23,27,29,28, and 20 presented an MRE above 1.00%, with the last two standing out owing to value of 2.375% for an Ɛ/D of 10 -6 and an Re of 4 × 10³. For Offor & Alabi (2016), the minimum value of RE was 0.005% for an Ɛ/D of 5 × 10 -6 and an Re of 10 8 , and the maximum RE value was 2.128% for an Ɛ/D of 5 × 10 -6 and an Re of 4 × 10³.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Any effort to present a simple full-range solution for the friction factor would be of practical importance. Offor & Alabi (2016) suggested a new equation for the friction factor that focuses on precision and computational efficiency. Vatankhah (2018) proposed analytical solutions for the Colebrook equation with a minimal number of natural logarithms and noninteger powers (lower computational cost).…”
Section: Introductionmentioning
confidence: 99%